2017
DOI: 10.1001/jama.2017.3096
|View full text |Cite
|
Sign up to set email alerts
|

Genomics, Health Disparities, and Missed Opportunities for the Nation’s Research Agenda

Abstract: The completion of the Human Genome Project occurred at a time of increasing public attention to health disparities. In 2004, Sankar and colleagues 1 suggested that this coincidental timing resulted in an inappropriate emphasis on the contribution of genomics to health disparities, conflating racial patterns of disease with genetic ancestry, and distracting attention from the large and compelling body of scientific evidence pointing to social determinants of health disparities. 2 For example, genomic research h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 9 publications
0
64
0
Order By: Relevance
“…Kashyap and colleagues note that, although the role of genomics in health disparities is quite complex, it is critical to understand how genetic variation influences the health and well‐being of at‐risk communities to eliminate health disparities in the USA . On the other hand, West et al . argue that clarification of genetic contributors to disease etiology will not help to provide ways to address disparities, as they are rooted in social, material, and environmental conditions.…”
Section: Genomic Studies Of Bipolar Disorder: Underrepresentation Of mentioning
confidence: 99%
“…Kashyap and colleagues note that, although the role of genomics in health disparities is quite complex, it is critical to understand how genetic variation influences the health and well‐being of at‐risk communities to eliminate health disparities in the USA . On the other hand, West et al . argue that clarification of genetic contributors to disease etiology will not help to provide ways to address disparities, as they are rooted in social, material, and environmental conditions.…”
Section: Genomic Studies Of Bipolar Disorder: Underrepresentation Of mentioning
confidence: 99%
“…Shawneequa L. Callier, JD, MA 1,2 Scholars have shown that promoting diversity and inclusion in precision medicine research is important for ethical and scientific reasons. The processes for classifying the populations that enroll in biomedical research, however, are often unclear, inconsistent, and poorly justified.…”
Section: The Use Of Racial Categories In Precision Medicine Researchmentioning
confidence: 99%
“…Genomic approaches, however, are insufficient to address the various social experiences that often correlate with poor health. 2 Discrimination in housing and employment, inadequate access to health insurance, and implicit and explicit biases in medical care, for example, substantially impact health outcomes, long-term health, and health disparities. 3(p135),4(p38) For these reasons, precision medicine studies that measure the effects of social, cultural, and environmental influences on health are essential to improve health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The arguments of genetic determinists obscure the hard work of parsing apart the true impact that genetic differences may have on population health, 35 and instead rest on a presumed understanding that "from both an objective and scientific (genetic and epidemiologic) perspective there is great validity in racial/ethnic self-categorizations, both from the research and public policy points of view." 23 The threat to precision medicine this view represents includes an oversimplification of diagnostic and therapeutic decisions that will be imprecise and inaccurate.…”
Section: Commentary: Precision Medicine Equity -Matthewmentioning
confidence: 99%